Effects of bee bread supplementation during recovery on time trial performance and selected physiological parameters (Funded Work) - CHEE KEONG CHEN,; FADZEL WONG CHEE PING,; FOONG KIEW OOI,; MAHANEEM MOHAMED, (International Journal of Pharma and Bio Sciences, 2018)
This study investigated the effects of bee bread supplementation during recovery on subsequent running time trial performance and selected physiological parameters. Twelve athletes were recruited in this randomised cross-over study. During the experimental trials, participants ran on a treadmill for 90 min and then rested for four hours. During this recovery period, participants consumed either 30 g.h-1 of bee bread or placebo. Heart rate and tympanic temperature were measured at intervals of 20 min during this period. Blood samples were collected to determine plasma glucose, haemoglobin and hematocrit. Then the participants performed a 20 min running time trial on a treadmill. Statistical analyses were performed using ANOVA with repeated measures and paired t test. The distance covered in the bee bread trial was significantly further than placebo trial (3.45 ± 0.4 km vs 3.24 ± 0.4 km respectively). Plasma glucose in the bee bread trial was significantly higher compared to the placebo trial during the recovery. However, heart rate, oxygen uptake, tympanic temperature, and plasma volume in the bee bread trial were not significantly different from the placebo trial. In conclusion, supplementation of bee bread during recovery seems to have improved subsequent running time trial performance.